Socialization Of Clean & Healthy Living Behavior Management For The School Community - Arfa Adha; Salsabilah, Salsabilah; Rahmad Diyanto; Aidil Syaputra; Purwanto, Purwanto; Agung Hilmi Wahdi; Lubis, Ade Evriansyah (Journal Management of Sport, 2025)
The purpose of this activity is to increase students' knowledge and awareness about PHBS in schools and always apply it in everyday life. The method of implementing Community Service activities is in the form of socialization with the lecture method to participants at SMK Migas Bumi Melayu Riau, then given leaflets about socialization about PHBS in Schools as many as 30 participants. Based on the results of the evaluation of students' knowledge and understanding of PHBS in schools during community service, it shows an increase in knowledge and understanding with a total score of more or equal to 90%. The material presented can be understood by all socialization participants and is felt to be very useful, which in turn can change the behavior of students at SMK Migas Bumi Melayu Riau in a better and positive direction, namely realizing the importance of implementing PHBS in schools and in everyday life. The conclusion is that the increased knowledge and understanding of the socialization participants about PHBS in schools. It is recommended to all participants who do not know and understand about PHBS in schools, so that they can increase their knowledge and understanding of PHBS at SMK Migas Bumi Melayu Riau.